OPTIMIZATION OF CROSS-PLATFORM APPLICATIONS USING THE REACT LIBRARY - Kutsenko Olexandr; Bezverhiy Olexandr (World Science, 2024)
In today’s world, with the growing use of mobile devices, the importance of creating cross-platform applications that provide high performance and quality of user experience has increased significantly. Improving the creation of such applications using React and React Native opens up wide opportunities for developers due to the possibility of code reuse, high development speed and ease of innovation, and is especially relevant because it concerns not only the technological aspects of development, but also economic efficiency, quality of user experience and the speed of introducing innovations to the software market. Open source and active community communication allow rapid identification and resolution of issues, development of new features and enhancements, and the sharing of knowledge and experience between developers. This creates a positive environment for innovation and growth, promotes rapid technological progress, and improves the quality of end products. The paper analyzes the key aspects and challenges associated with the creation of cross-platform applications, analyzes the main types of optimizations at different levels of development, including the component level, the state and data level, the level of working with APIs and external data, as well as the loading and code level. Special attention is paid to the integration of synchronous and asynchronous rendering to achieve optimal performance and user experience. Highlights the benefits of flexible state management using state managers, as well as the importance of image and media optimization to improve overall website performance. The article notes the role of the developer community in the process of improvement and innovation. Developers who master these technologies and optimize their application can create products that not only meet the requirements of the time, but also form new standards in the field of mobile and web development. Further research and integration of the latest technologies into the development process of cross-platform applications will have a significant impact on the software industry.